STRATEGI KOMUNIKASI DINAS SOSIAL KABUPATEN SUKOHARJO DALAM PROGRAM KARTU INDONESIA SEHAT (KIS) DI KELURAHAN GAYAM - UTAMI, ANISA DWI (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2018)
Communication strategy has important role in a communication process. In the government institution, communication strategy is very needed for process in delivering message or program instigation that will be arranged from the government to the society. The function of government institution is a place for society in expressing their opinions, it can make the government institution it is possible to do mutual communication well and effectively. It due to the fact that the information and message deliver to society can be absorb well so there will not be wrong line or miss communication. This research is conducted in Kabupaten Sukoharjo Social Service Agency and the subject of the research is poor society who recived KIS program. Kabupaten Sukoharjo Social Service Agency implements five step models of communication strategy from Hafied Cangara which are Penelitian (Research), Perencanaan (Plan), Pelaksanaan (Execution), Pengukuran (Measurement) and Pelaporan (Reporting). Besides, it also implements information integration theory and changes of attitude from Heath and Littlejohn that mention information as attitude influence tools, the attitude is difficult to change, attitude Variable influence: Valence and weight of information and application of information integration theory in practice and public relations research. Base of the results, it can be known that communication strategy implemented by Kabupaten Sukoharjo Social Service Agency use five step five models of communication strategy from Hafied Cangara and also the change of attitude from Heath and Littlejohn. It also show that communication strategy has already applied appropiate although there are some obstacles such as technical, semantics, physical problems & organuk and also culture.